NILAI PENDIDIKAN DALAM SIMBOLISME RITUAL SELAMETAN: Studi tentang Tradisi Mitoni di Desa Damarjati Kalinyamatan Jepara - Alfiana, Nur (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2019)
This study aims to find out how the implementation and meaning of the mitoni tradition with its various samples in the Damarjati Village, Kalinyamatan Jepara. Through the implementation of the mitoni tradition, research also seeks to identify the educational value contained in it. This type of research is qualitative using descriptive analysis method. Data analysis techniques using content analysis (content analysis). The results of this study indicate that in the implementation of Mitoni take the time of the Maghrib, coinciding with the full moon. After the invited guests are complete, then the host issues menus that have been prepared. In addition to the menu, in the mitoni tradition, there are wisdom symbols contained, such as sega golong. Judging from the manufacturing process must be "Iyan" first. The symbol means the process of creating the world and everything in it. Klanding is symbolized by the character of authority, mbayung, symbolized by the fetus ajan has a generous nature, has been lying, symbolized will not experience shortcomings, sega uduk, symbolized has a high social sensitivity, sega buju kroyok, symbolized by devout worship, cengkak cengkak, symbolized will not experience deficiencies, sega uduk, symbolized has a high social sensitivity, sega buju kroyok, symbolized by devout worship, cengkak cengkak, symbolized for not having deficiencies, sega uduk, symbolized has a high social sensitivity, sega buju kroyok, symbolized by devout worship, cengkak cengkak, symbolized for not having deficiencies, Key Word: Education, Selametan, Mitoni